Temporal and epidemiological analysis of tuberculosis cases in the state of Piauí, Brazil (Research, Society and Development, 2020)
Tuberculosis is a chronic infectious and transmissible disease. It is acquired by inhaling Mycobacterium tuberculosis, which is present in the air when an infected individual coughs, sneezes, or even talks and expels particles contaminated by this agent. It mainly affects the lungs, but can also affect the kidneys, bones and meninges. Thus, this study aimed to analyze the epidemiological situation of tuberculosis in the state of Piauí from 2014 to 2018. The variables analyzed were: age group, gender, race, confirmed cases by year of diagnosis, number of cases reported in the municipalities, type of entry, incidence rate, clinical form of TB, closure situation and associated comorbidities. The analysis was performed using the data provided by SINAN/DATASUS. The following results were obtained, 2018 was the year with the highest number of notifications (843), males were the most affected in all the years analyzed, the most common clinical form was pulmonary tuberculosis, the most prevalent comorbidities were alcoholism, smoking and diabetes, the most common type of entry was new; in the situation of entry the highest percentage was the cure, however, ignored/white obtained a higher number in 2018. In addition, the most affected age group was 40 to 50 years, followed by 20 to 39 years; the cities with the highest number of cases were Teresina and Parnaíba; however, the cities with the highest incidence were Bom Princípio, Parnaíba and Cocal de Telha; the highest incidence rate occurred in 2018, and finally, the brown race showed the highest number of cases.